Parenting Stress, Social Support, and Mother-Child Interactions in Families of Multiple and Singleton Preterm Toddlers - Lutz, Kristin F. (2012)
The study investigated family support as a buffer of stress in 153 mothers and preterm toddlers. Data were collected regarding maternal depressive symptoms, parenting stress, and family support; infant health; and videotaped mother-child interactions. Although more parenting stress related to less optimal child play, only information support functioned as a protective factor. Information support predicted positive play under high, but not low, maternal stress. Mothers of multiples reported more parenting stress than mothers of singletons.